Electrical wiring industrial - Smith, Robert L. 1926- (Delmar Cengage Learning, 2008)
Guides readers through the wiring of an entire industrial building. This book shows readers how to incorporate codes and principles into everyday practice and procedures. It also includes industrial building plans, offering opportunities for practice in interpreting and applying Code requirements to sitework, feeder bus systems, and panelboards.